PENGARUH PENYULUHAN DENGAN MEDIA VIDEO ANIMASI DAN POSTER TERHADAP PENGETAHUAN GIZI SEIMBANG PADA ANAK USIA SEKOLAH DI MAJELIS TAKLIM AL MANSYURIAH BOGOR TAHUN 2020 - Arfia Kalih Hakim (2021)
Nutritional problems that are prone to occur in school children are caused by unhealthy lifestyles and low knowledge of nutrition and health. One of the efforts that can be made to overcome nutritional problems is to provide counseling to increase knowledge of balanced nutrition in children by using animation video and posters. This study used a total sampling technique with a sample of 48 respondents. The research method used is a quasi-experimental with pre-post test two group design with parametric analysis T-test. The results showed that the balanced nutritional knowledge of school children in the Al-Mansyuriah counseling group with poster media increased to a sufficient category (65.2%), and in the counseling group with animation video increased to a good category (80%). Based on the bivariate results, there is a difference in increasing knowledge of balanced nutrition with poster media counseling and animation video (p-value 0,000). The conclusion is there is an increase in knowledge after being given counseling with posters and animation video, but animation video was more effective than poster in increasing knowledge of balanced nutrition in school children (P value 0.001).